Outcomes and Prognostic Factors in Cirrhotic Patients with Acute Variceal Bleeding and Hepatocellular Carcinoma: A Nested Case–Control Study - Liu G; Xiao S; Xiang T; Wang X; Shen Y; Yang L; Luo X (Journal of Hepatocellular Carcinoma)
Guofeng Liu,* Songchi Xiao,* Tong Xiang, Xiaoze Wang, Yi Shen, Li Yang, Xuefeng Luo Department of Gastroenterology and Hepatology, Sichuan University-University of Oxford Huaxi Joint Centre for Gastrointestinal Cancer, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xuefeng Luo; Li Yang, Department of Gastroenterology and Hepatology, Sichuan University-University of Oxford Huaxi Joint Centre for Gastrointestinal Cancer, West China Hospital, Sichuan University 37 Guoxue Lane, Chengdu, Sichuan, 610041, People’s Republic of China, Email luo_xuefeng@wchscu.cn; yangli_hx@scu.edu.cnPurpose: The treatment outcomes and risk factors for the prognosis of acute variceal bleeding (AVB) in hepatocellular carcinoma (HCC) patients remain unclear. Hence, we assessed the clinical outcomes and prognostic factors of these patients.Methods: This study retrospectively enrolled 1532 AVB patients with cirrhosis from January 2016 to December 2022. Of these patients, 310 had HCC, and after 1:1 individual matching, 306 of them were matched with 306 patients without HCC. Six-week mortality, one-year mortality, and five-day treatment failure were recorded.Results: In the matched-pair analysis, patients with HCC had a higher rate of 6-week and 1-year mortality than those without HCC (6-week: 24.5% vs 7.8%, P < 0.001; 1-year: 45.9% vs 16.2%, P < 0.001). The rate of 5-day treatment failure was similar between the two groups (21.1% vs 16.7%, P = 0.213). Among AVB patients with HCC, the multivariate analysis revealed that the Child-Pugh score (HR, 1.239, 95% CI, 1.121– 1.370; P < 0.001) and Barcelona Clinic Liver Cancer (BCLC) stage (C-D vs 0-B) (HR, 14.409; 95% CI, 5.758– 36.055; P < 0.001) were independently associated with 6-week mortality. Moreover, the rate of 6-week mortality was 60.2% in patients who had a high Child-Pugh score (≥ 9) and advanced BCLC stage (C–D), much higher than in those with low Child-Pugh score (< 9) and earlier BCLC stage (0-B) (P < 0.001).Conclusion: Among patients with cirrhosis and AVB, patients with HCC had significantly worse outcomes than those without. The severity of liver disease and the stage of HCC are the main determinants of mortality in HCC patients.Keywords: acute variceal bleeding, hepatocellular carcinoma, cirrhosis, portal hypertension